2020
DOI: 10.1177/0042098020912980
|View full text |Cite
|
Sign up to set email alerts
|

Does the monocentric model work in a polycentric urban system? An examination of German metropolitan regions

Abstract: In explaining the determinants of urban spatial structure, researchers have relied on the traditional monocentric ‘Alonso-Mills-Muth’ model. This article contributes to this discussion by testing the viability of the monocentric model when applied to metropolitan areas in Germany, a country traditionally associated with a polycentric urban structure, regional differences and urban shrinkage. We estimate the model with a unique dataset covering 92 metropolitan areas over two time periods (2000 and 2014), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
3
5
1
Order By: Relevance
“…Third, as predicted by the SUM, higher agricultural land prices decrease urbanized areas. This result confirms those of Oueslati et al (2015) and Paulsen (2012), whereas Spivey (2008) and Schmidt et al (2020) found mixed or non-robust results.…”
Section: Assessing Sum Predictions On Urbanized Areas Surfacesupporting
confidence: 87%
See 4 more Smart Citations
“…Third, as predicted by the SUM, higher agricultural land prices decrease urbanized areas. This result confirms those of Oueslati et al (2015) and Paulsen (2012), whereas Spivey (2008) and Schmidt et al (2020) found mixed or non-robust results.…”
Section: Assessing Sum Predictions On Urbanized Areas Surfacesupporting
confidence: 87%
“…Second, higher incomes also significantly increase urban areas, in line with the predictions of the SUM and of Paulsen (2012), Oueslati et al (2015), and Schmidt et al (2020), but in contradiction with Spivey (2008). Spivey (2008), working on US cities, find a negative and significant impact of incomes on urban areas, which she explains by the fact that the increase in incomes increases the demand for more affordable housing farther from the city center, but also raises the opportunity cost of time, the second effect outweighing the first one.…”
Section: Assessing Sum Predictions On Urbanized Areas Surfacesupporting
confidence: 79%
See 3 more Smart Citations